Analisis Pengendalian Persediaan Bahan Baku Catring Makanan Menggunakan Metode Min-Max Stock - Halawa, Yeriaman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Catering Business is a home business that runs on food supplies or catering. Inventory can be defined as raw materials stored for use in the future. However, the quantity of inventory should not be too large so that the capital invested in inventory and the resulting costs are not too large and should not be too small because it can slow down the production process. These materials must always be available to ensure the production process runs smoothly. Therefore, it is necessary to plan and control raw materials. Inventory control is a very important issue, because the amount of inventory will determine or influence the smoothness of the production process as well as the effectiveness and efficiency of the business. The raw material inventory control method used in this research is the min-max stock method. The min-max stock method is a raw material control method which is based on the assumption that raw material inventory is at two levels, namely the maximum level and the minimum level. If the maximum level and minimum level have been set, then when the inventory reaches the minimum level an order for raw materials must be made to place the inventory at the maximum level. This is to avoid inventory amounts that are too large or too small. The application of the min-max method is carried out so that the warehouse can know what minimum stock must be in the warehouse to meet production quantity capacity and what the maximum stock of raw materials in the warehouse is to avoid wasting inventory costs.